Exploring the therapeutic potential of Saudi Kleinia anteuphorbium (L.) DC. Essential oil: Insights into antioxidant, analgesic, and hepatorenal protective effects - Hanan Y. Aati; Mohamed Seif; Mahmoud Emam; Jawaher Al-Qahtani; Hala Attia; Sultan Aati; Juergen Wanner (Heliyon, 2024)
Lately, the herb's essential oils have received the intense attention of researchers and pharmaceutical agencies. The chemical composition, antioxidant, analgesic activity, anti-hyperpyrexia, and hepatorenal protective effects of the Kleinia anteuphorbium (L.) DC. Essential oil (KAEO) were evaluated. The KAEO was yanked by steam distillation and subjected to a GC/MS system. The antioxidant powers of KAEO were evaluated by DPPH, NO, and FRAP tests. Besides the anti-hyperpyrexia, the analgesic effects were assessed. Moreover, the hepatorenal curative effects were evaluated in a carbon tetrachloride-rat model. Sixty-eight active components were identified by GC/MS. α-pinene was the most dominant monoterpene in KAEO. KAEO showed anti-hyperpyrexia, anti-captive, and great antioxidant powers through DPPH, NO, and FRAP. The oral LD50 of KAEO was 187.5 mg/kg in rats. Furthermore, KAEO treatment succeeded in reliving the adverse effects of CCL4 in rats as a standard toxic model through reliving the hepatic pathological and oxidative stress and restoring the hepatic and renal functions. Overall, the obtained results demonstrated that KAEO might be used as a potential natural medicine to relieve a variety of modern symptoms and hepatorenal disorders associated with oxidative stress.